Allelopathic Effect of Artemisia Persica Boiss. Aqueous Extract on Seed Germination and Seedling Growth of Selected Brassica Varieties - Tawab, Faiza; Inayat, Naila; Mustafa, Mahnoor; Gul, Asma Niaz; Gul, Ansa; Wadood, Asma; Wali, Shumaila (Indus Journal of Bioscience Research, 2025)
An experiment was conducted during 2024 at Shaheed Benazir Bhutto Women University, Peshawar laboratory to find out the allelopathic effect of hot water extracts of Artemisia persica Boiss. on seed development and seedling progression of selected varieties of Brassica; Nifa Gold, Sarso T20 and Durr-e-Nifa. Different concentrations (10g, 15g and 20g) of aqueous extract of Artemisia persica Boiss. revealed significant reduction in seed development seedling progression of tested brassica varieties. Seeds germination, plumule and radicle lengths, dry and wet weights were expressively reduced in test treatments linked to control. Higher concentration of the extract (20g) had significantly reduced the germination percentage to 10% as compared to control condition. Nifa Gold was the most susceptible variety to higher concentration of the extract which showed minimum seed development. Radicle and plumule lengths, dry and wet weights were lowest at 15g concentration of the applied extract of Artemisia persica Boiss. while moisture content was not significantly affected. Allelopathic effects were more obvious at higher concentrations then lower in most conditions. The results showed differences in allelopathic effects on all three varieties at different concentrations.